The structure of collective-bargaining in Northern Ireland, 1973-84 - Harris, RID; Wass, VJ (Economic & Social Studies, 1988)
A unique database (the New Earnings Survey) is used to look at collective bargaining structures in 1973 and 1984. A comparison is made with the structures existing in Great Britain, and some attempts are made to identify the determinants of different types of bargaining structures.
Keywords: Collective bargaining - Ireland; New Earnings Survey